Visual reconstruction of Novopokrovskaya Church in Rostov-on-Don - Petrusenko, Yuliya; Ivanova-Ilicheva, Anna (project baikal, 2021)
The article analyses the graphic reconstruction of the lost Novopokrovskaya Church in Rosov-on-Don by architect N. M. Sokolov. The goal was to carry out visual reconstruction of the lost historic building on the basis of historical and archival studying of documents and extant images, as well as field studies. The history of the construction of the Novopokrovskaya Church was studied. The visual reconstruction of the church lost in the modern urban environment was carried out.